The description of Indonesian student mathematics literacy in the last decade - Aisyah Aisyah; Dadang Juandi (SAINTIS Publishing, 2022)
This study aims to describe the mathematical literacy of Indonesian students based on research articles published in the last decade. This study used a systematic literature review method by collecting 163 relevant journals and then re-selected to meet the inclusion criteria and the criteria for assessing the quality of study results. It was found information on the development of research analyzing the mathematical literacy of Indonesian students starting from elementary school, junior high school, high school, and College Level. The literacy level of students at the elementary level is still considered low, while at the junior high school level it is assessed from various perspectives ranging from the low mathematical literacy of students to the factors that influence it. At the high school level, students' mathematical literacy is also still low even though a mathematical literacy test has been carried out in the Indonesian context. Finally, mathematical literacy at the university level is found that different student learning styles will go hand in hand with different mathematical literacy abilities.